CREATION OF THE DANCE MUSIC FOR THE PUCUK BANG MASCOT OF BANGLI REGENCY - Garwa, I Ketut (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2024)
Pucuk Bang, or Hibiscus Rosa-Sinensis, was established as the identity and mascot of Bangli Regency during the leadership of Regent I.B. Gede Agung Ladip (1990–1995, 1995–2000) and officially declared on Bangli's 771st anniversary on May 10, 1991. Regent Sang Nyoman Sedana Arta (2021–2026) aimed to revive Bangli's taksu through the creation of the Pucuk Bang Dance as a visual icon, communication medium, identity symbol, and representation of Bangli’s vision and mission, fostering emotional connections and broad acceptance. The Pucuk Bang flower embodies purity, love, sincerity, and courage. "Pucuk" symbolizes the peak or forefront, and "Bang" (red) represents bravery, spirit, and the deity Brahma, a manifestation of God. It reflects courage and rising to the top with purity, love, and sincerity. The Pucuk Bang concept was transformed into a creative work integrating music, dance, and technology, deeply exploring textures, shapes, colors, and meanings. Inspired by Bangli’s heritage, such as Baris dances and Gong Gede gamelans, it uses the Tri Angga structure (kawitan, pangawak, pangecet). The musical work is united by nine dancers symbolizing the Universe's greatness as Sarining Padma Bhuwana. The Pucuk Bang flower embodies purity, love, sincerity, and courage. "Pucuk" symbolizes the peak or forefront, and "Bang" (red) represents bravery, spirit, and the deity Brahma, a manifestation of God. It reflects courage and rising to the top with purity, love, and sincerity. The Pucuk Bang concept was transformed into a creative work integrating music, dance, and technology, deeply exploring textures, shapes, colors, and meanings. Inspired by Bangli’s heritage, such as Baris dances and Gong Gede gamelans, it uses the Tri Angga structure (kawitan, pangawak, pangecet). The musical work is united by nine dancers symbolizing the Universe's greatness as Sarining Padma Bhuwana.